Going live with tumor exosomes and microvesicles. Issue 2 (4th March 2017) - Hyenne, Vincent; Lefebvre, Olivier; Goetz, Jacky G.
ABSTRACT: Tumor extracellular vesicles (EVs), including exosomes, emerged as key drivers of the pro-tumorigenic dialog between the tumor mass and its microenvironment by mediating long and short distance communication. In vitro studies defined the capacity of tumor EVs to modify the phenotypes of stromal and tumor cells. These studies are now supported by a growing number of functional in vivo experiments. Remarkably, they allowed the identification of a new role for tumor EVs in priming the pre-metastatic niches (PMN). Several molecules transported in tumor EVs (RNAs and proteins) have recently been found to be essential for tumor progression and metastasis in vivo . In parallel, novel EV labeling and tracking strategies have very recently allowed the first descriptions of tumor EVs in vivo and pave the way for a better understanding of their function in realistic pathophysiological contexts. Here, we review the functional approaches and the recent progress in in vivo imaging of EVs, which have refined our understanding of the role played by tumor EVs. Finally, we emphasize the remaining challenges and open questions related to the biology of tumor EVs.